(x+5)=(3x-2)

Simple and best practice solution for (x+5)=(3x-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+5)=(3x-2) equation:


Simplifying
(x + 5) = (3x + -2)

Reorder the terms:
(5 + x) = (3x + -2)

Remove parenthesis around (5 + x)
5 + x = (3x + -2)

Reorder the terms:
5 + x = (-2 + 3x)

Remove parenthesis around (-2 + 3x)
5 + x = -2 + 3x

Solving
5 + x = -2 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
5 + x + -3x = -2 + 3x + -3x

Combine like terms: x + -3x = -2x
5 + -2x = -2 + 3x + -3x

Combine like terms: 3x + -3x = 0
5 + -2x = -2 + 0
5 + -2x = -2

Add '-5' to each side of the equation.
5 + -5 + -2x = -2 + -5

Combine like terms: 5 + -5 = 0
0 + -2x = -2 + -5
-2x = -2 + -5

Combine like terms: -2 + -5 = -7
-2x = -7

Divide each side by '-2'.
x = 3.5

Simplifying
x = 3.5

See similar equations:

| 11/30x360 | | 7x^2+8xy+y^2=45 | | (5v-9)(8-v)=0 | | ((12v^6)-(14v^3))/(2v^3) | | 2mx^2+3mx=0 | | 2(4x-3)=58 | | 2(x-2)+3x=6x+7-(x-3) | | 15x-220=5x-10 | | 16-11x+12=-16x | | -2x-7+3x=2(5x-9) | | 3e/(e^x) | | 159*200000/X=8.50 | | 2-55m-5=73 | | 32x+48=11-x-7 | | 2(3x-5)=2x-1 | | (2n+6)(4n+2)+16=80 | | 2n^2-40=-11n | | 8n+1=13+2n+8n | | V^2-2vf+f^2=0 | | 3=7cos(2x) | | 3-18x-6=3 | | y=7cos(2x) | | 175+2(100)= | | 9x-124=3x-10 | | 3(2x+5)+3x=42 | | 5(3x-4)-6x=4x+8 | | (7t+6)+(3t+x)+(4t+y)=48 | | t^3+6t-4t-24=0 | | 175.00+3.00x=630 | | X^2-64i^2=0 | | 4+3lnx=17 | | 3p^2-4=p |

Equations solver categories